Pornographic Discourse on Social Media from a Feminist Theory Perspective - M. Gufran Haramain; Yunita Indinabila; Ulyan Nasri (FAKULTAS DAKWAH UIN SALATIGA, 2024)
This research aims to explore the views of feminist activism from a liberal and radical perspective towards pornography on social media platforms. The research method used is qualitative descriptive and applies a literature review approach. The research results show that liberal feminist activists view women as having the right to freedom regarding pornography, including the right to create, publish, display, distribute, and consume pornography in a closed environment. In contrast, radical feminist activism views pornography as part of the social structure as a patriarchal agenda equivalent to global capitalism that exploits and oppresses women. The research conclusion emphasizes that pornography, from the perspective of feminist theory, is not neutral and carries the goal of ideological domination in a culture that empowers women to become objects. The implications of this research stimulate critical thinking regarding the need to change views regarding pornography in a society that values ​​gender equality.